Eye, retina, and visual system of the mouse [ - Chalupa, Leo M.; Williams, Robert W. , 1952- (MIT Press, 2008)
A comprehensive guide to current research, reflecting recent technical breakthroughs that have established the usefulness of the mouse model as part of a bilateral exchange between experimental and clinical research